PRE-REFERRAL PROGRAM DEVELOPMENT - Leri Septiani; Hidayat Wijayanegara; Lina Herlina (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Background: Indonesia's healthcare system is designed with tiered referrals, involving primary, secondary, and tertiary services that work synergistically to provide optimal care. The pre-referral stage is an important element in this system, where patients receive initial treatment at primary health facilities before being referred to higher levels. This stage aims to ensure proper initial care as well as quick and effective referrals according to the patient's condition. However, the implementation of pre-referral programs often faces obstacles such as limited primary health facilities, lack of coordination between facilities, and difficulty accessing supporting information technology. Objective: to analyze the development of a pre-referral program to improve the effectiveness of patient referrals. Research method: Participatory Action Research (PAR) approach, involving Community Health Center and hospitals under the coordination of the Subang Health Office for six months (November 2023-April 2024). The sample consisted of three Community Health Center and five hospitals selected based on their capacity to handle obstetric cases. Data were collected through a Likert scale questionnaire to measure the feasibility of pre-referral media. Results: The results showed that the pre-referral back sheet had high validity (99.6%) and could be used. Interviews revealed problems such as delays in the referral process due to incomplete medical information and inconsistent documentation standards. Conclusion: The importance of periodic evaluation of this program to ensure its sustainability and effectiveness is emphasized. Health worker feedback as well as evaluation of patient care outcomes should be used for continuous improvement in the obstetric referral system.